Targeting of non-apoptotic cancer cell death mechanisms by quercetin: Implications in cancer therapy - Yang, Hao; Xu, Shan; Tang, Lidan; Gong, Jinhong; Fang, Hufeng; Wei, Jifu; Su, Dan (Frontiers in Pharmacology, 2022)
The ultimate goal of cancer treatment is to kill cancer cells, based on the use of various therapeutic agents, such as chemotherapy, radiotherapy, or targeted therapy drugs. Most drugs exert their therapeutic effects on cancer by targeting apoptosis. However, alterations in apoptosis-related molecules and thus assisting cells to evade death, eventually lead to tumor cell resistance to therapeutic drugs. The increased incidence of non-apoptotic cell death modes such as induced autophagy, mitotic catastrophe, senescence, and necrosis is beneficial to overcoming multidrug resistance mediated by apoptosis resistance in tumor cells. Therefore, investigating the function and mechanism of drug-induced non-apoptotic cell death modes has positive implications for the development of new anti-cancer drugs and therapeutic strategies. Phytochemicals show strong potential as an alternative or complementary medicine for alleviating various types of cancer. Quercetin is a flavonoid compound widely found in the daily diet that demonstrates a significant role in inhibiting numerous human cancers. In addition to direct pro-tumor cell apoptosis, both in vivo and in vitro experiments have shown that quercetin exerts anti-tumor properties by triggering diverse non-apoptotic cell death modes. This review summarized the current status of research on the molecular mechanisms and targets through which quercetin-mediated non-apoptotic mode of cancer cell death, including autophagic cell death, senescence, mitotic catastrophe, ferroptosis, necroptosis, etc.